Association between the C-reactive protein to albumin ratio and adverse clinical prognosis in patients with young stroke - Du, Yang; Zhang, Jia; Li, Ning; Guo, Jiahuan; Liu, Xinmin; Bian, Liheng; Zhao, Xingquan; Liu, Yanfang (Frontiers in Neurology, 2022)
Background The inflammatory response plays an important role in ischemic stroke, and the incidence of stroke in young adults has increased rapidly in recent years. The C-reactive protein-to-albumin ratio (CAR) is a new index that reflects the overall inflammatory status of patients with major diseases; however, no studies have reported the relationship between CAR and young stroke. Methods The participants' baseline characteristics and laboratory examination results, including CAR, were obtained at admission. The modified Rankin Scale (mRS) scores at the 30-day and 90-day follow-ups were obtained from all patients. All the participants included in the study were classified into four groups according to CAR quartiles (Q1–Q4). Logistic regression was used to analyze the relationship between different CAR levels and adverse outcomes (mRS 3–6 and mRS 2–6). We also plotted receiver operating characteristic curves of CAR for adverse clinical outcomes and calculated the area under the curve and cutoff values. Results A total of 630 patients with young stroke were enrolled in the study. In the multivariate logistic regression model, at the 30-day follow-up, the Q3 and Q4 (significantly increased CAR) groups showed an elevated risk of mRS score of 2–6 (odds ratio [OR]: 2.94; 95% confidence interval [CI]: 1.40–6.16, p < 0.01; OR: 4.01; 95% CI: 1.88–8.91, p < 0.01). At the 90-day follow-up, the Q3 and Q4 groups still showed an elevated risk of an mRS score of 2–6 (Q3, OR: 2.76; 95% CI: 1.30–5.86, p < 0.01; Q4, OR: 2.63; 95% CI: 1.22–5.65, p < 0.01). Conclusion A significantly increased CAR was independently associated with an increased risk of adverse outcomes in young patients with stroke.